Bismuth shield affecting CT image quality and radiation dose in adjacent and distant zones relative to shielding surface: A phantom study - Ying-Lan Liao; Nan-Ku Lai; Yeu-Sheng Tyan; Hui-Yu Tsai (Biomedical Journal, 2019)
Background: To quantify image quality and radiation doses in regions adjacent to and distant from bismuth shields in computed tomography (CT). Methods: An American College of Radiology accreditation phantom with four solid rods embedded in a water-like background was scanned to verify CT number (CTN) accuracy when using bismuth shields. CTNs, image noise, and contrast-to-noise ratios (CNRs) were determined in the phantom at 80–140 kVp. Image quality was investigated on image portions in the zones adjacent (A zone) to and distant (D zone) from a bismuth shield. Surface radiation doses were measured using thermoluminescent dosimeters. Streak artefacts were graded on a 3-point-scale. Results: Changes in CTN caused by a bismuth shield resulted in changes in X-ray spectra. CTN changes were more apparent in the A zone than in the D zone, particularly for a low tube voltage. The degrees of CTN changes and image noise were proportional to the thickness of the bismuth shields. A 1-ply bismuth shield reduced surface radiation doses by 7.2%–15.5%. The overall CNRs were slightly degraded, and streak artefacts were acceptable. Conclusions: Using a bismuth shield could result in significant CTN changes and perceivable artefacts, particularly for a superficial organ close to the shield, and is not recommended for quantification CT examinations or follow-up CT examinations. Keywords: Computed tomography, Radiation protection, Bismuth shielding, Quantification analysis, Image quality